La epidemia del cólera de 1833 y la mortalidad en la ciudad de México - Velasco, María del Pilar (El Colegio de México A.C., 1992)
This is a new attempt to understand the functioning of vital statistics during the nineteenth century, wich analyzes the death rate caused by cholera morbus in Mexico City during the year 1833. Although this was not the only such epidemic, it was the first, and given that it was so widespread, its impact was felt at all levels of the social, economic, and political life of the metropolis.On the basis of data estimated by numerous authors concerning the total volume of the population and various statistical and demographic methods, Velasco calculated the probable population of Mexico City in 1833 and its age and sex composition.Parish archives were the basis for estimating mortality levels. Abbreviated life tables were calculated, by sex, for 1832 and 1833, and in an effort to assess the specific weight of cholera in overall mortality, additional tables were prepared according to cause of death.From a strictly demographic viewpoint, it is observed that almost 5% of Mexico City's total population died from cholera; that the 1 200 males and females under the age of four who died from the epidemic left incomplete generations in the long term, that the disappearance of nearly 2 700 persons between the ages of 15 and 44 affected men and women of childbearing age, that when eliminating the deaths due to cholera, life expectancy at birth would have been 12.3 years higher for men and 13.95 years for women.From another perspective, it is pointed out that the health measures implemented during the epidemic brought about significant changes in the social, economic, and urban organization of the city and that, as of that time, social differentiation in the face of death was even more evident.